STRATEGI PENINGKATAN KEUNGGULAN BERSAING IKM: PERAN PEMBELAJARAN ORGANISASI DAN INOVASI - Sugiono, Edi; Efendi, Suryono (Jurnal Riset Manajemen dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 2019)
This study aims to analyze the role of organizational learning and innovation in improving the competitive advantage of small and medium enterprises (SMEs) in the Mojokerto area. The study was conducted using primary data obtained from the distribution of questionnaires. In total, there were 100 IKM leaders in Mojokerto who became the respondents in this study. Hypothesis testing is done by using Partial Least Square Structural Equation Modeling (SEM-PLS). The results of the study show that organizational learning and innovation have a positive and significant effect on improving SMEs’ competitive advantage. The results of this study also prove that innovation can mediate the relationship between organizational learning and SMEs’ competitive advantage.